2019
DOI: 10.1186/s12933-019-0971-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycemic variability with left ventricular diastolic function in type 2 diabetes mellitus

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a major cause of heart failure (HF) with preserved ejection fraction (HFpEF), usually presenting as left ventricular (LV) diastolic dysfunction. Thus, LV diastolic function should be considered a crucial marker of a preclinical form of DM-related cardiac dysfunction. However, the impact of glycemic variability (GV) on LV diastolic function in such patients remains unclear.MethodsWe studied 100 asymptomatic T2DM patients with preserved LV ejection fraction (LVEF) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Abundant evidence has indicated that increased long-term GV, assessed by long-term fluctuations of HbA1c or FPG, can predict the risk of CVD [ 14 , 40 44 ] in patients with T2DM, the prognosis of acute lung diseases in patients with DM [ 45 ], and malignancies in the general population [ 46 ]. Increased GV after transcatheter aortic valve implantation is associated with an increased risk of major complications within 30 days [ 47 ], and reducing GV may represent a new therapeutic strategy for preventing the development of heart failure with preserved ejection fraction in patients with T2DM [ 48 ]. In addition, combining GV and HbA1c may achieve the highest accuracy for determining thrombotic risk [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abundant evidence has indicated that increased long-term GV, assessed by long-term fluctuations of HbA1c or FPG, can predict the risk of CVD [ 14 , 40 44 ] in patients with T2DM, the prognosis of acute lung diseases in patients with DM [ 45 ], and malignancies in the general population [ 46 ]. Increased GV after transcatheter aortic valve implantation is associated with an increased risk of major complications within 30 days [ 47 ], and reducing GV may represent a new therapeutic strategy for preventing the development of heart failure with preserved ejection fraction in patients with T2DM [ 48 ]. In addition, combining GV and HbA1c may achieve the highest accuracy for determining thrombotic risk [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic cardiomyopathy, LV diastolic dysfunction has been suggested as the earliest functional change detectable and is almost always present prior to signs of LV systolic dysfunction [ 27 ]. Hypertension, ageing and diabetes are all associated with an increased risk of developing diastolic dysfunction [ 28 30 ], and recently it has been shown that higher glycemic variability may be associated with LV diastolic dysfunction independent of HbA1c [ 31 ]. Recent studies have shown, that treatment with SGLT-2 inhibitors dapagliflozin [ 32 ] or canagliflozin [ 33 ] can improve LV diastolic function in patients with type 2 diabetes, and that SGLT-2 inhibitors may play a future role in prevention and treatment of cardiovascular disease in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, detrimental effects of GV on patients with diabetes have been proposed for various medical conditions [ 7 13 ]. GV could not only predict diabetic vascular complications [ 7 , 14 , 15 ], heart failure [ 9 ], and postoperative complications of aortic valve implantation [ 11 ], but also indicate poor prognosis for in-patients with acute lung diseases [ 8 ] and acute coronary syndrome [ 13 ]. Moreover, because GV could modify the correlation between time in range and estimated HbA1c, GV consideration was recommended when setting individualized goals for glycemic control [ 10 ].…”
Section: Introductionmentioning
confidence: 99%